2012
DOI: 10.1111/jph.12037
|View full text |Cite
|
Sign up to set email alerts
|

Visual Detection of Potato leafroll virus by One‐step Reverse Transcription Loop‐Mediated Isothermal Amplification of DNA with Hydroxynaphthol Blue Dye

Abstract: Loop‐mediated isothermal amplification (LAMP) assay is a novel technique for amplifying DNA under constant temperature, with high specificity, sensitivity, rapidity and efficiency. We applied reverse transcription loop‐mediated isothermal amplification (RT‐LAMP) to visually detect Potato leafroll virus. One‐step RT‐LAMP was performed using RNA of PLRV‐infected potato leaves and a set of primers (F3, B3, FIP, BIP, LF and LB) designed for RT‐LAMP reaction of the coat protein (CP) gene of PLRV. Positive effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 35 publications
0
40
0
Order By: Relevance
“…Since there is no effective viricide to control of the viruses in potato, using virus free seed potatoes is an effective approach for management of potato viral disease. In Iranian seed potato market, along with other part of the world, demands for certified potato seed tubers are increasing [2][3]30]. In order to produce infection free potato seed tubers, using rapid, cost-effective and sensitive methods for detection of important potato viruses, including PLRV, in different stages of infection process would provide a great step forward.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since there is no effective viricide to control of the viruses in potato, using virus free seed potatoes is an effective approach for management of potato viral disease. In Iranian seed potato market, along with other part of the world, demands for certified potato seed tubers are increasing [2][3]30]. In order to produce infection free potato seed tubers, using rapid, cost-effective and sensitive methods for detection of important potato viruses, including PLRV, in different stages of infection process would provide a great step forward.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, numerous studies in both plants and animals have been reported to recognize pathogens by LAMP technique. For instance, RT-LAMP method were utilized for detection of Plasmodium falciparum gametocytes [9], Fusarium graminearum [23], Peste des petits ruminants virus (PPRV) [24], Potato virus Y (PVY) [10], Japanese yam mosaic potyvirus (JYMV) [22], Rabies virus (RABV) [19], Macrobrachium rosenbergii noda virus (MrNV) [25], Cymbidium *Corresponding author: Mohammad Amin Almasi, Department of Plant Biotechnology, Faculty of Agriculture, University of Zanjan, Zanjan, Iran, E-mail: aminalmasi66@gmail.com mosaic virus (CymMV) [26] and Potato Leafroll Virus (PLRV) [2,3]. As described earlier, some different visualizing systems are employed for verification of LAMP products.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations